Mapping the binding interface between an HIV-1 inhibiting intrabody and the viral protein Rev. - Thomas Vercruysse (Public Library of Science (PLoS), 2013)
HIV-1 Rev is the key protein in the nucleocytoplasmic export and expression of the late viral mRNAs. An important aspect for its function is its ability to multimerize on these mRNAs. We have recently identified a llama single-domain antibody (Nb190) as the first inhibitor targeting the Rev multimerization function in cells. This nanobody is a potent intracellular antibody that efficiently inhibits HIV-1 viral production. In order to gain insight into the Nb190-Rev interaction interface, we performed mutational and docking studies to map the interface between the nanobody paratope and the Rev epitope. Alanine mutants of the hyper-variable domains of Nb190 and the Rev multimerization domains were evaluated in different assays measuring Nb190-Rev interaction or viral production. Seven residues within Nb190 and five Rev residues are demonstrated to be crucial for epitope recognition. These experimental data were used to perform docking experiments and map the Nb190-Rev structural interface. This Nb190-Rev interaction model can guide further studies of the Nb190 effect on HIV-1 Rev function and could serve as starting point for the rational development of smaller entities binding to the Nb190 epitope, aimed at interfering with protein-protein interactions of the Rev N-terminal domain.